Assisted reproduction - principles, procedures, and their effectiveness - Řežábek, Karel; Moosová, Martina; Jirsová, Simona (Casopis lekaru ceskych, 2023)
Assisted reproduction is an integral part of infertility treatment. The basic method is in vitro fertilisation (IVF), and intracytoplasmic sperm injection into the oocyte, cryopreservation of sperm, oocytes and embryos is also commonly used. The proportion of embryos tested with preimplantation genetic testing (PGT) for chromosomal aneuploidy or defects in specific genes is increasing. The use of donated oocytes is also significant, particularly because of the depletion of ovarian reserve in women over 40 years of age. The effectiveness of treatment is always very fundamentally dependent on the age of the woman. Assisted reproductive treatment is very well available in the Czech Republic, as is fertility preservation by sperm/oocyte freezing.
Keywords: genetické testování; Reproduction; Semen; Retrospective Studies; Cryopreservation; Middle Aged; mužské pohlaví; PGT; Adult; IVF; intracytoplazmatické injekce spermie; Fertilization in Vitro; success rate; Oocytes; ženské pohlaví; oocyty; retrospektivní studie; Humans; sperma; lidé středního věku; trends; Sperm Injections, Intracytoplasmic; rozmnožování; fertilizace in vitro; dospělí; assisted reproduction; Genetic Testing; Female; lidé; Male